2014
DOI: 10.1111/jac.12087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simulating Drought in Various Phenophases on the Water Use Efficiency of Winter Wheat

Abstract: In Central Europe, drought is the most important limiting factor for autumnsown cereals. Due to the decline in groundwater, it is a priority to use less waterdemanding forms of crop production. Water use efficiency (WUE) can only be increased if cultivars with satisfactory water management traits are grown, so that they can exploit the water reserves of the soil even if drought occurs during the vegetation. Water consumption and water use efficiency of winter wheat genotypes were investigated in a model experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 35 publications
3
28
1
1
Order By: Relevance
“…In general, it has been pointed out that wheat cultivars exposed to drought stress are able to flower earlier and, hence, bring the grain filling period forward, helping the plants to avoid the adverse effects of the drought and harsh climate [8,91,92]. This study suggested that the use of CTD and SPAD as appropriate selection criteria for breeding programs in Jordan is extremely useful since both parameters showed highly positive correlation with grain yield and significant variations existed with respect to the cultivars and water regimes applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, it has been pointed out that wheat cultivars exposed to drought stress are able to flower earlier and, hence, bring the grain filling period forward, helping the plants to avoid the adverse effects of the drought and harsh climate [8,91,92]. This study suggested that the use of CTD and SPAD as appropriate selection criteria for breeding programs in Jordan is extremely useful since both parameters showed highly positive correlation with grain yield and significant variations existed with respect to the cultivars and water regimes applied.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the needs of a dramatically increasing population, annual wheat production must increase from the current level (below 1%) to at least 1.6% [3]. Therefore, all agricultural policies must be directed toward enhancing wheat production by developing a global strategic agenda for wheat research, encouraging efficient investment in wheat research, and developing genotypes tolerant to both biotic and abiotic stress conditions-knowing that the available water reserves worldwide are limited and declining continuously [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data are directly available and no further calculations are necessary, as the model provides a realtime precipitation value for each grid cell online. 12 b. Phenology data Wheat plants are sensitive to a low water supply in the growing phases of stem elongation-ear emergence, ear emergence-yellow ripeness, or stem elongationyellow ripeness 13 (Farooq et al 2012;Conradt et al 2015b;Varga et al 2015). To represent this sensitivity, we used two ways of designing index accumulation periods: (i) a fixed accumulation period and (ii) a flexible accumulation period based on phenology reports (Table 2).…”
Section: October 2016 D a L H A U S A N D F I N G E Rmentioning
confidence: 99%
“…Research on transpiration response to water availability for winter wheat has also been conducted [2] . In some areas, water deficit is one of the main limiting factors in cereal production [3,4] . Water content in wheat leaf was up to 40%-80% that has a great influence on its growing period [5] .…”
Section: Introductionmentioning
confidence: 99%